New Perspectives on Desensitization in the Current Era - An Overview - Kumar, Vineeta; Locke, Jayme E. (Frontiers in Immunology, 2021)
Blood group and tissue incompatibilities remain significant barriers to achieving transplantation. Although no patient should be labeled "un-transplantable" due to blood group or tissue incompatibility, all candidates should be provided with individualized and realistic counseling regarding their anticipated wait times for deceased donor or kidney paired donation matching, with early referral to expert centers for desensitization when needed. Vital is the careful selection of patients whose health status is such that desensitizing treatment is less likely to cause serious harm and whose anti-HLA antibody status is such that treatment is likely to accomplish the goal of increasing organ offers with an acceptable final crossmatch. Exciting new developments have re-energized the interest and scope of desensitization in the times ahead.